Development and Evaluation of Lactose-Free Single-Unit and Multiple-Unit Preparations of a BCS Class II Drug, Rivaroxaban - Daniel Zakowiecki; Peter Edinger; Markos Papaioannou; Michael Wagner; Tobias Hess; Jadwiga Paszkowska; Marcela Staniszewska; Daria Myslitska; Michal Smolenski; Justyna Dobosz; Grzegorz Garbacz; Dorota Haznar Garbacz (MDPI AG, 2024)
Background/Objectives: The aim of the present study was to develop lactose-free formulations of rivaroxaban, a novel oral anticoagulant used for the treatment and prevention of blood clotting. As a BCS Class II drug, rivaroxaban is characterized by poor solubility in aqueous media, posing a significant formulation challenge. Methods: To address this, phosphate-based excipients were employed to prepare both traditional single-unit dosage forms (tablets) and modern multiple-unit pellet systems (MUPS). These formulations were successfully developed and thoroughly evaluated for their physical properties and performance. Results: The resulting formulations demonstrated very good mechanical strength, including appropriate hardness and friability, alongside strong chemical stability. Their dissolution profiles met the requirements of the compendial monograph for Rivaroxaban Tablets and were comparable to those of the reference product, Xarelto® film-coated tablets. Conclusions: This study shows the potential for producing effective, stable, and patient-friendly medications that meet the needs of contemporary society, where an increasing number of individuals suffer from lactose intolerance or seek vegan-friendly alternatives.